Study of Students' Concept Understanding and Argumentation Levels of Material Magnets at Class VI-IX Level - Yohana Idamina Betty; I Wayan Dasna; Widiyanti Widiyanti (Jurnal Penelitian Pendidikan IPA, 2023)
This study airms to examine differences in understunding the concept of magnets and arguments about magnets at different grade levels. This type of research is survey research. The research subjects consisted of 188 students spread across different grade levels and school in the city of Kupang, namely class VI of elementary school, class VII of junior high school and class IX of junior high school. The method used is the ex post facto method using test instrumens and interview. The data analysis used is the difference test and correlation test. The conclusion obtained after carrying out the research proces and data testing is that there are differences in understanding of the concept of magnets between class VI students who are currently learning about magnets in class VI, class IX students who are currently studying magnets and have studeied magnets in class VI. There are differences in the level of magneic argumentation between class VI students who are currently learning about magnets, class VII students who have studied magnets in class VI and grade IX students who are currently studying magnets and have stidied magnets in grade VI.Â  There is no correlation between understunding of the concept and level of argumentation of magnetic material in class VI elementary school students and class VII students of junior high school.